The Emergency Medicine Events Register: An analysis of the first 150 incidents entered into a novel, online incident reporting registry. (31st July 2016) - Hansen, Kim; Schultz, Timothy; Crock, Carmel; Deakin, Anita; Runciman, William; Gosbell, Andrew
Abstract: Objective: Incident reporting systems are critical to understanding adverse events, in order to create preventative and corrective strategies. There are very few systems dedicated to Emergency Medicine with published results. All EDs in Australia and New Zealand were contacted to encourage the use of an Emergency Medicine – specific online reporting system called the Emergency Medicine Events Register (EMER). Methods: We conducted an analysis of the first 150 incidents entered into EMER. EMER captures Emergency‐medicine‐specific details including triage score, clinical presentation, outcome, contributing factors, mitigating factors, other specialities involved and patient journey stage. These details were analysed by an expert panel. Results: Over the first 26 months, 150 incidents were reported into EMER. The most common categories reported, in order, were diagnostic error, procedural complication and investigation errors. Most incidents contained more than one category of error. The most common stage of the patient's journey in which an incident was detected was after discharge from the ED. Conclusion: A focus on correct diagnosis, procedure performance and investigation interpretation may reduce errors in the ED. The ability to learn from incidents and make system changes to enhance patient safety in healthcare organisations is an inherent part of providing a proactive, quality culture.